Rotavirus infection as a cause watery diarrhea - Mohammad F. Ibraheem (مجلة كلية الطب, 2013)
Summary Background: Rotavirus infection is the most commoncause of watery viral diarrhea in children younger than 5 years of age; it is a major cause of childhood morbidity and mortality. Objective:The aim of the study is todetermine the clinical picture, age distribution of patients with rotavirus infection and their maternal educational background. Patients &methods: A total of 202 patients suffering from diarrhea were included in this study, over 6 months period( from 1stof March 2011to 30th of August 2011),in Children Welfare Teaching hospital. History and physical examinationwere carried out, anthropometrics measures were done and plotted on Centers for Disease Control& World Health Organization charts to determine the nutritional status.Stool was collected for General stoolexamination, stool PH, stool culture and stool for rotavirus antigen. Results: The study showed that41 children out of202 were rotavirus positive (20.29%) , and (192) (94.69%) of diarrhea occur below 2 years of age mainly between 6-12 months old(138) (68,32%), most of the mothers of the patients were illiterate (78)(38.6%),all of the patients were dehydrated and with the other clinical features( diarrhea ,vomiting ,fever).Most of the cases of rotavirus infection occurred with mixed feed children23/41(57%). Conclusions: Rotavirus infection is an important cause of diarrhea especially in the last 6 months of the first year of life.Poor maternal educationis risk factors in occurrence of diarrhea. Keywords: watery diarrhea, rotavirus infection.